2019
DOI: 10.1017/jmo.2019.54
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating organizational compassion in healthcare

Abstract: The compassion of healthcare workers towards patients is widely recognized, but research suggests a dearth of compassion among co-workers. Indeed, workplace bullying and negative employee outcomes are over-represented in the healthcare sector (including burnout and substantial staff turnover). In this paper, we discuss the cultivation of compassion for healthcare workers, using the lens of positive organizational scholarship. Our concern is not only with the individual level compassion (i.e. between employees)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 59 publications
3
53
0
Order By: Relevance
“…The results depicted that supervisor undermining triggers compassion in the workplace. This finding is consistent with the theoretical reasoning that negative social interactions and suffering in the workplace trigger compassionate responses (Dutton et al, 2014;Eldor, 2018;Simpson et al, 2020). Moreover, our findings are also consistent with the results of other studies, which found a positive association between workplace stressors and experienced compassion (Chu, 2016;Eldor, 2018;Madden et al, 2012;Rhee et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The results depicted that supervisor undermining triggers compassion in the workplace. This finding is consistent with the theoretical reasoning that negative social interactions and suffering in the workplace trigger compassionate responses (Dutton et al, 2014;Eldor, 2018;Simpson et al, 2020). Moreover, our findings are also consistent with the results of other studies, which found a positive association between workplace stressors and experienced compassion (Chu, 2016;Eldor, 2018;Madden et al, 2012;Rhee et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Due to environmental and systems-level issues, less concrete aspects of care related to personcentredness, including engaging in conversations, are thus exchanged in favour of clinical tasks (Ludlow et al, 2020). As further identified by Simpson et al (2020), workplace disharmony can develop when resources, including available time, are scarce, resulting in low levels of compassion being extended to colleagues.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“….to make the best decision for the person" (RN1). By intentionally collaborating to reduce work-related stress, the teams displayed attributes of organisational compassion described by Simpson et al (2020). Effective two-way communication between residents, their family and the care home further facilitated quality care: "We're working on providing each resident a holistic approach.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Crewe (2019) and Simpson (2019) and their respective colleagues collectively drew attention to organisational capacity-building. Via an international study, Crewe and Girardi (2019) considered positive deviance among nurse managers that served to enhance positive organisational outcomes; while Simpson and Farr-Wharton (2019) empirically demonstrated how to build compassionate health services.…”
Section: Why Is Posh Needed?mentioning
confidence: 99%
“…Equally important is research on the role of the ‘paradox mindset phenomena… to better understand positive deviance’, including tensions between ‘positive and negative’ deviance (Crewe & Girardi, 2019). Inspired by Simpson and Farr-Wharton (2019), it would be helpful to know who should assume responsibility for ‘embedding compassion within… [an] organization’, why, how and the associated implications – be they intended or unintended? Although this special issue illuminates ‘relational-centred care’ (Kippist, Fulop, Dadich, & Smyth, 2019), there is now opportunity to examine its other manifestations, as well as the parameters that demarcate ‘high-quality connections and relational coordination’.…”
Section: Where To Next?mentioning
confidence: 99%